Pengodean Kasus Cedera, Keracunan Dan External Cause Pada Sistem Informasi Puskesmas - Hendra; Prawirya, Ais; Sulaiman, Sulaiman; Rohman, Hendra; Fadia, Fadia (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2024)
In health center, there was still errors in filling in disease codes. In this case was on cases of injury, poisoning and external cause codes that were not coded up to the 5th character. This happened because doctors and nurses did not understand the coding procedures. This study aims to identify coding process, calculate the percentage of code accuracy, identify factors causing inaccuracy in coding injuries, poisoning and external causes at the Bambanglipuro Health Center. The provision of disease diagnosis codes at health center was carried out after the nurse had finished filling in the assessment, doctor input diagnosis in SIMPUS, and ICD code automatically appeared. The percentage of correct diagnosis codes for cases of poisoning injuries and external causes of outpatients at Bambanglipuro Health Center, Bantul in period 2023 from a total sample of 71 medical records, number of correct diagnosis codes was 20 medical records (28%), and number of incorrect diagnosis codes was 51 medical records (72%). The cause was human factor (human), namely human resources who did not meet the competence of medical creators, special training had not been provided for coding officers and external causes were not coded. Method factors are that there is no SOP on disease coding system. Measuring implementation of disease diagnosis coding is carried out by re-examination by medical record officers who have competence in disease coding. Fulfilment of human resources according to qualifications affects work outcomes in UKRM. The ICD database on SIMPUS needs to be reviewed and data updated by vendors so that code selection can be available more specifically. Classification of code determination with ICD rules can describe the journey of a patient's medical record history more specifically.